Primary and secondary structural features in the eastern portion of the South Mountain Batholith, southwestern Nova Scotia: implications form regional stress orientations during intrusion - Horne, R.; Corey, M.; Ham, L.; MacDonalad, H. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1988)
Primary flow features (schlleren banding, negacryat-xenollth alignment end blotlte foliation) within the eastern portion of the South Mountain Bathollth (SMB) reflect the geometry of intrusions and divides the study area into two distinct domains. In the eastern half the primary flow features display roughly concentric to random regional patterns related to differential flowage near contacts. Northeast-trending linear patterns characterize the western half and may in part reflect regional stress. Stereonet evaluation of prominent joints, dykes and veins Indicate four primary-regional joint sets (trends), all of which are steeply dipping. The dominant joints, trends 2 (063 ) and 4 (145 ) form a roughly orthogonal pair parallel and perpendicular, respectively, to the regional fold axes. Trends 3 (130 ) and 5 (164 ) form a conjugate set around trend 4. Quartz vein orientations coincide with trend 4 end maxima of dykes correspond to trends 3, 4 and 5. Trends 2 to 5 are Interpreted as resulting from horizontal compression parallel to trend 4 during a period of uplift. Trend 1 (042 ) is associated with a major fault zone which has locally been superimposed on the pattern of primary-regional joints. Primary-regional joints have to some degree influenced the intrusion of the later phases of the SMB. Mineralization within the SMB Is strongly controlled by the regional fracture patterns. Oraniuo mineralization generally occurs within altered trend 2 joints uhereas polymetallic veln-grelsen mineralization is generally associated with trend 4 joints.